HUBUNGAN ANTARA PEMBERDAYAAN DENGAN KEPUASAN KERJA KARYAWAN DI PT. BATAVIA BINTANG BERLIAN PULOGADUNG - Leoni Santika; Henry Eryanto; M maisaroh (Faculty of Economics, State University of Jakarta., 2014)
This study aims to determine whether there is a relationship between empowerment and job satisfaction in employees at PT. Batavia Bintang Berlian in Jakarta Timur. The research was carried out for 3 months from April 2014 to June 2014. The method used was a survey method with the correlation approach. The study population was all employees in the PT. Batavia Bintang Berlian Showroom Mitsubishi, amounting to 120 employees, and affordable population of this study is that employees are placed in marketing totaled 60 people. The samples are 51 respondents using proportional random sampling. To collect data from both variables, the instruments used for the variable X (Empowerment) and Y variables (Job satisfaction) is shaped questionnaire. Before use, test the construct validity (Construct Validity) through the validation process is the calculation of the correlation coefficient score points with the total score and reliability tests with Cronbach alpha formula. Result reliability of the instrument variable X (Empowerment) of 0,899 and instrument variable Y (Job satisfaction) of 0.936. The test requirements analysis was to find the regression equation obtained was Y = 37.32 + 0.717 X. Liliefors normality test results produced L count = 0.065 and L table = 0.124 at significance level (a) = 0.05 for the number of samples (n) = 51. Because L count = (0.065) < L table = (0.124) then the variables X and Y are normally distributed. Testing the hypothesis by testing the significance of regression produces F count= 37.40 > f table = (4.04), which means that the regression equation is significant. Linearity regression test produces F count = 0.72 and F table = 2.05 so F count < F table table it can be concluded that the model is a linear regression equation. Product moment correlation coefficient test result r count = 0.658. further test the significance of the correlation coefficient using t-test, yielding t count = (6.12) > t table = (1,68). Results of these studies concluded that there is a positive relationship between empowerment and job satisfaction in employees. With a coefficient of determination or determining test results obtained 43.29% job satisfaction variable (Y) is determined by the empowerment (X).